Child online safety and parental intervention: a study of Sri Lankan internet users. Issue 3 (4th June 2018) - Tennakoon, Hemamali; Saridakis, George; Mohammed, Anne-Marie
Abstract : Purpose: Today's world of digital and mobile media does not require actual physical contact, between the suitable target and the motivated offender, as with traditional crime. In fact, as Mesch (2009) contended that the internet is not merely an information channel but it creates a new space of activities for children, where they are exposed to motivated offenders and the actors of fourth party. Therefore, for the sake of children's safety, the practice of parental mediation control is increasingly becoming more pertinent everyday. Thus, the purpose of this paper is to examine how parental mediation control in Sri Lanka is influenced by their internet self-efficacy, their experience as online victims and their trust in online users. Design/methodology/approach: This paper uses a unique data set of computer and internet users from Sir Lanka to examine parental intervention in their children's online activities. Specifically, the data set contains 347 responses from computer and internet users. To analyze the data, the authors use a binary dependent (probit) model. Findings: The results show that such factors alter the baseline probability of parental intervention. However, some differences are found between younger and older parents, with the latter group responding more to trust in online users and victimization experience while the former is mainly driven from computer self-efficacy. In particular, the older group is less likely to trust online internet users in terms of never adding unknown persons in the social media. Finally, being self-employed and an older parent has a positive effect on the likelihood of adopting parental controls, possibly because of the non-pecuniary attributes of self-employment. Originality/value: This study adds to the emerging parental mediation control literature by looking at the likelihood of younger and older parents who were victims of cybercrimes, who have greater internet self-efficacy and lower online third-party trust to adopt parental mediation control behaviors. Also another contribution to the literature is the role of occupation type on parental monitoring behaviors.